The chef - Patterson, James, 1947-; DiLallo, Max (Little, Brown and Company, 2019)
Accused of committing murder in the line of duty, detective Caleb Rooney of the New Orleans PD uses the contacts from his moonlighting job as a celebrity food-truck chef to counter a terrorist plot.